Outside ownership in the hedge fund industry - Mullally, Kevin A. (Journal of Banking & Finance, 2022)
I examine an action hedge fund managers take to increase their assets under management: selling ownership stakes in their firms to outside owners. Fund companies that sell stakes to outside owners open more new funds and attract higher fund flows. The flow impact is greater for funds who sell stakes to more reputable outside owners and outsiders with asset management divisions. Funds with outside owners do not subsequently outperform their peers. Despite the lack of subsequent outperformance, fund investors do benefit from a reduction in returns management and lower incidence of fraud. Taken together, my results indicate that these transactions result in synergies for all parties involved.